2006
DOI: 10.1051/0004-6361:20052653
|View full text |Cite
|
Sign up to set email alerts
|

A search for fine structure inside high resolution profiles of weak diffuse interstellar bands

Abstract: This paper presents a survey of the high-resolution profiles of selected, moderately weak diffuse interstellar bands (DIBs) between 4725 and 6730 Å. In very high signal-to-noise spectra, obtained as a result of averaging several individual exposures of reddened, early-type stars that show Doppler splitting of <2 km s −1 in interstellar gas lines, the profiles seem to have a substructure. This supports the molecular origin hypothesis for DIBs. We studied the profiles of the diffuse interstellar bands at wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…8. Its profile has been described by Słyk et al (2006) but no substructures have been found in the relatively low resolution. In the HARPS spectrum of HD 147165, the substructures are too weak to be traced with certainty.…”
Section: Resultsmentioning
confidence: 99%
“…8. Its profile has been described by Słyk et al (2006) but no substructures have been found in the relatively low resolution. In the HARPS spectrum of HD 147165, the substructures are too weak to be traced with certainty.…”
Section: Resultsmentioning
confidence: 99%
“…For example, visual inspection of the stellar He II 5876 Å line in Fig. 1 shows that HD 149757 and HD 185418 are fast rotators while HD 23180, HD 24398, HD 203532, and HD 170740 have narrower photospheric lines; in these latter cases, we checked even more carefully for the presence of narrow stellar lines in the DIB spectral regions that could mimic DIBs or DIB sub-structures (see the cases of 4727, 4963, 5541, 5546, 5762, 6729; Table 3 from Słyk et al 2006). In the case of the 4734, 5170, 5175, and 6729 Å DIBs, we found that the continuum is contaminated by stellar lines that fall just outside the DIB and, as shown in Figs.…”
Section: Extraction Of Individual C 2 -Dibsmentioning
confidence: 99%
“…Most of the strong and narrow optical DIBs have been found to have asymmetric profiles, and in the case of the strongest ones such as DIBs 5797 and 6614 Å (Sarre et al 1995;Ehrenfreund & Foing 1996;Galazutdinov et al 2002), 5850, 6234, and 6270 Å (e.g., Krełowski & Schmidt 1997;Galazutdinov et al 2002), 6376, 6379, and 6196 Å (Walker et al 2001), sub-structures have been clearly identified which may be consistent with unresolved rotational branch structures associated with electronic transitions of gas-phase molecules. Profiles of several C 2 -DIBs and some other weak DIBs have been examined also by Galazutdinov et al (2002) and Słyk et al (2006). Asymmetries were found, but in the case of the weak C 2 -DIBs these were only seen for the 4963, 5418, 5512, 5541, and 5546 Å bands.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution, high-S/N ratio spectra have revealed substructure (and variations in that substructure) in a number of the DIBs (Sarre et al 1995;Kre lowski & Schmidt 1997;Kerr et al 1998;Galazutdinov et al 2002Slyk et al 2006), though on velocity scales much smaller than those discussed later in this paper. Ehrenfreund & Foing (1996) interpreted the structure seen in the commonly observed portions of the λλ5797.1, 6379.2, and 6613.6 DIBs as representing rotational contours of large gas-phase molecules.…”
Section: Introductionmentioning
confidence: 77%